2017
DOI: 10.17221/138/2016-pps
|View full text |Cite
|
Sign up to set email alerts
|

Woolly ash aphid - is the alien bug posing a threat to European ash trees? - a review

Abstract: Hałaj R., Osiadacz B. (2017): Woolly ash aphid -is the alien bug posing a threat to European ash trees? -a review. Plant Protect. Sci., 53: 127-133.Prociphilus (Meliarhizophagus) fraxinifolii (Riley, 1879) (Hemiptera: Eriosomatidae) is an alien species in Europe that has been spreading quickly there. This paper presents the origin and current occurrence, classification, description, identification, and biology of this species. It also discusses the harmfulness and threats, especially the impact on hostplants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Outside the native range P. fraxinifolii was initially recorded only on species introduced from North America: F. pennsylvanica, F. americana , and F. velutina , so it was suggested that P. fraxinifolii did not affect native ash trees in Europe (C oeur d’acier et al ., 2010; P érez H idalgo & M ier D urante , 2012). But then P. fraxinifolii was also found on European ash F. excelsior (H ałaj & O siadacz , 2017). We have yet found P. fraxinifolii only on F. pennsylvanica, because F. excelsior is rare in Moscow.…”
Section: Biology and Harmfulnessmentioning
confidence: 99%
See 4 more Smart Citations
“…Outside the native range P. fraxinifolii was initially recorded only on species introduced from North America: F. pennsylvanica, F. americana , and F. velutina , so it was suggested that P. fraxinifolii did not affect native ash trees in Europe (C oeur d’acier et al ., 2010; P érez H idalgo & M ier D urante , 2012). But then P. fraxinifolii was also found on European ash F. excelsior (H ałaj & O siadacz , 2017). We have yet found P. fraxinifolii only on F. pennsylvanica, because F. excelsior is rare in Moscow.…”
Section: Biology and Harmfulnessmentioning
confidence: 99%
“…Prociphilus fraxinifolii is monoecious, i.e. does not change host plants during its life cycle (H ałaj & O siadacz , 2017). This feature distinguishes it from other European representatives of the genus feeding on ash trees.…”
Section: Biology and Harmfulnessmentioning
confidence: 99%
See 3 more Smart Citations